La Société Royale Économique des Amis du Pays de Saint-Jacques-de-Compostelle devant l'éclosion de la société de masse - Margarita Barral Martínez (Cahiers de Civilisation Espagnole Contemporaine)
The 18th century saw the Spanish university system still deeply stuck in the past, with regulations that virtually prevented the success of any attempted change. Neither the reform implemented by Ferdinand vi neither the subsequent ones undertook by Campomanes allowed higher education institutions to lead the process of scientific renewal that the Age of Enlightenment demanded. This resulted in the emergence of new scientific and educational institutions, such as academies, high schools and economic societies of friends of the country. This paper aims to analyse the decline of the Economic Society of Friends of the Country of Santiago de Compostela over the 20th century, when its purpose ceased to make sense in mass society. We will first tackle the origins and development of the institution throughout the 19th century, after which we will present the evolution of this entity over the 20th century so as to show that its role as an educational and training centre, which had remained valid from the start, became outdated in the face of new social demands in the educational field.This brief essay has been based on the consultation of the documents kept in the Archive of the Royal Economic Society of Friends of the Country of Santiago (hereinafter ARSEAPS), as well as bibliographic sources.